2024
DOI: 10.1523/eneuro.0437-23.2024
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Correlates of Individual Differences in Reinforcement Learning during Pain Avoidance and Reward Seeking

Thang M. Le,
Takeyuki Oba,
Luke Couch
et al.

Abstract: Organisms learn to gain reward and avoid punishment through action-outcome associations. Reinforcement learning (RL) offers a critical framework to understand individual differences in this associative learning by assessing learning rate, action bias, Pavlovian factor (i.e., the extent to which action values are influenced by stimulus values), and subjective impact of outcomes (i.e., motivation to seek reward and avoid punishment). Nevertheless, how these individual-level metrics are represented in the brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated behavioral individual differences in reinforcement learning paradigms ( Grunitzki et al, 2014 ; Aberg et al, 2016 ). Moreover, differences in neurophysiological responses have also been noted between reinforcement and non-reinforcement learners ( Smillie et al, 2011 ; Kaiser et al, 2018 ; Le et al, 2024 ). In the case of this study, reinforcement learners (i.e., those who maintain their performance) may have a greater overall ability to integrate the abstracted numerical feedback and may utilize different neural mechanisms to modify motor behavior, thus resulting in better retention compared to others within their group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated behavioral individual differences in reinforcement learning paradigms ( Grunitzki et al, 2014 ; Aberg et al, 2016 ). Moreover, differences in neurophysiological responses have also been noted between reinforcement and non-reinforcement learners ( Smillie et al, 2011 ; Kaiser et al, 2018 ; Le et al, 2024 ). In the case of this study, reinforcement learners (i.e., those who maintain their performance) may have a greater overall ability to integrate the abstracted numerical feedback and may utilize different neural mechanisms to modify motor behavior, thus resulting in better retention compared to others within their group.…”
Section: Discussionmentioning
confidence: 99%